Correlation Analysis Between Financial Ratios and Stock Prices of Real Estate Companies Listed on the Indonesia Stock Exchange - Sasabella (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
Indonesia’s real estate sector is experiencing a surge in investor interest, reflected by the increasing number of companies joining the Indonesia Stock Exchange (IDX). Understanding the factors influencing stock prices is crucial to navigate this dynamic landscape. This study delves into this question, aiming to identify key financial ratios that significantly impact the stock prices of real estate companies listed on the IDX. Employing multiple linear regression analysis, we examined 45 observations spanning three years, collected from 15 real estate firms on the IDX. The results shed light on the significant influence of two key financial ratios: Return on Assets (ROA) and Earnings per Share (EPS). Interestingly, ROA exhibited a negative relationship with stock prices. This suggests that while a company's overall profitability, as measured by ROA, might be improving, the market might perceive factors that could limit future growth, leading to a decline in stock prices. Conversely, Earnings per Share (EPS) displayed a positive correlation with stock prices. This aligns with investor expectations, as a company generating higher earnings per share is perceived as more financially sound and attractive, ultimately boosting its stock price. Ultimately, this study empowers investors to make informed decisions by going beyond a single financial ratio and considering the interplay between various financial metrics specific to the real estate industry. Keywords: Real Estate Sector, Current Ratio, Debt to Equity, Return on Assets, Earning per Share.